2022
DOI: 10.1371/journal.ppat.1010378
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ATP via enhanced miRNA-30b, 30c, and 30e downregulates the expression of CD73 in CD8+ T cells of HIV-infected individuals

Abstract: CD8+ T cells play a crucial role against chronic viral infections, however, their effector functions are influenced by the expression of co-stimulatory/inhibitory receptors. For example, CD73 works with CD39 to convert highly inflammatory ATP to adenosine. However, its expression on T cells in the context of viral infections has not been well defined. Here, we analyzed the expression of CD73 on human T cells in a cohort of 102 HIV-infected individuals including those on antiretroviral therapy (ART), ART-naïve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…The migration assay was performed using the CytoSelect migration assay kit (Cell Biolabs), as we have reported elsewhere [55,56]. PBMCs were starved overnight in FBS-free culture media.…”
Section: Migration Assaymentioning
confidence: 99%
“…The migration assay was performed using the CytoSelect migration assay kit (Cell Biolabs), as we have reported elsewhere [55,56]. PBMCs were starved overnight in FBS-free culture media.…”
Section: Migration Assaymentioning
confidence: 99%
“…Fresh blood was collected from human subjects infected with SARS-CoV-2 and the peripheral blood mononuclear cells (PBMCs) were isolated by gradient separation using Ficoll-Paque Premium (GE Healthcare, Chicago, USA) according to routine protocols ( 28 , 29 ). The research ethics boards at the University of Alberta approved blood collection from human subjects with protocol # Pro00099502.…”
Section: Methodsmentioning
confidence: 99%
“… 37 , 39 Multiple studies demonstrated how the dysregulation of miR-7-3p, miRNAs-30, miRNA-125b, miRNA-150, miR-186, miR-210, and miR-222 has a negative impact on viral infection. 40 43 These miRNAs were found to target genes of Dicer, NTNG1, EFNB2, CXCL12, or HRB (HIV-1 Rev-binding protein), and HIV-EP2 (HIV-1 enhancer-binding protein 2). 40 , 42 The downregulation of these genes eventually leads to reduce viral expression.…”
Section: Mirnas In Hiv Lifecyclementioning
confidence: 99%
“…37,39 Multiple studies demonstrated how the dysregulation of miR-7-3p, miRNAs-30, miRNA-125b, miRNA-150, miR-186, miR-210, and miR-222 has a negative impact on viral infection. [40][41][42][43] 48 Targets a Tat cofactor, Cyclin-T1 Inhibits HIV-1 via repression of cyclin-T1 miR-191-5p 49 Targets and inhibits expression of CCR1 and NUP50 Inhibits viral replication via target repression. miR-28 29,50 miR-125b 29,50 miR-150 29,50 miR-223 29,50 miR-382-5p 29,50 Target the 3′ UTR of HIV-1 mRNA Decreases CD4 + T-cell activation vmiRNAs vmiR88 51 vmiR99 51 Mediates TNF-α release Facilitates immune activation miR-H1 25 Targets AATF, c-Myc and Dicer Promotes HIV replication miR-TAR 26,27 Targets AGO proteins, Caspase 8, Aiolos, and NPM/ B23…”
Section: Therapeutic Advances In Vaccines and Immunotherapy Mirnas Di...mentioning
confidence: 99%